2019
DOI: 10.5603/cj.a2018.0016
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale closure versus medical therapy after cryptogenic stroke: An updated meta-analysis of all randomized clinical trials

Abstract: Background: Cryptogenic strokes can be attributed to paradoxical emboli through patent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The incidence rate of adverse events was more than reported in clinical trials of closure for stroke. 21 In a prospective, single-centre study including non-PFO divers, divers with PFO and divers with closed PFO, the incidence rate of treated DCS (what corresponds to 'confirmed' DCS in our study) was reduced in both PFO groups in the post-intervention period. 20 However, the total burden of subjectively reported DCS increased in the PFO group after intervention while in the no-PFO and the closed-PFO groups the incidence rates decreased, as in our study.…”
Section: Discussionmentioning
confidence: 46%
“…The incidence rate of adverse events was more than reported in clinical trials of closure for stroke. 21 In a prospective, single-centre study including non-PFO divers, divers with PFO and divers with closed PFO, the incidence rate of treated DCS (what corresponds to 'confirmed' DCS in our study) was reduced in both PFO groups in the post-intervention period. 20 However, the total burden of subjectively reported DCS increased in the PFO group after intervention while in the no-PFO and the closed-PFO groups the incidence rates decreased, as in our study.…”
Section: Discussionmentioning
confidence: 46%
“…Until 2017, the results of CLOSE [ 7 ], Gore REDUCE [ 8 ], and Long-Term Outcomes of RESPECT study [ 6 ] showed that PFO closure significantly reduced the recurrence rate of ischemic stroke in patients with CS. Multiple trial-level meta-analyses have confirmed the efficacy of closure, yielding an odds ratio (OR) of 0.44 compared with MT alone [ 9 , 22 24 ]. Subgroup analyses showed the benefit of PFO closure was significant in patients with PFO associated with substantial RLS or ASA [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] In reviewing the literature, some studies. [ 19 ] reported that paradoxical embolism was the main mechanism of CS caused by PFO. [ 20 ] However, only a small number of patients with CS could find the source of paradoxical embolism.…”
Section: Discussionmentioning
confidence: 99%